Interpreting the meaning of changes in hippocampal volume associated with vestibular loss - Smith, Paul F. (Frontiers in Integrative Neuroscience, 2023)
Many studies have documented cognitive deficits, especially spatial cognitive deficits, in patients with some form of vestibular loss. Almost 20 years ago, hippocampal (HPC) atrophy was reported to be correlated with spatial memory deficits in such patients and the idea has gradually emerged that HPC atrophy may be causally responsible for the cognitive deficits. However, the results of studies of HPC volume following vestibular loss have not always been consistent, and a number of studies have reported no evidence of HPC atrophy. This paper argues that HPC atrophy, if it does occur following vestibular loss, may not be directly, causally responsible for the cognitive deficits, and that it is more likely that rapid functional changes in the HPC are responsible, due to the interruption of the transmission of vestibular information to the HPC. The argument presented here rests on 3 tranches of evidence: (1) Cognitive deficits have been observed in humans even in the absence of HPC atrophy; (2) HPC atrophy has not been reported in animal studies following vestibular loss, despite cognitive deficits; and (3) Animal studies have shown that the interruption of the transmission of vestibular information to the HPC has immediate consequences for HPC place cells, far too quickly to be explained by HPC atrophy. It is possible that HPC atrophy, when it does occur, is related to the longer-term consquences of living with vestibular loss, which are likely to increase circulating cortisol.